Clinical implications of measurable residual disease in AML: Review of current evidence. (January 2019) - Moors, Ine; Vandepoele, Karl; Philippé, Jan; Deeren, Dries; Selleslag, Dominik; Breems, Dimitri; Straetmans, Nicole; Kerre, Tessa; Denys, Barbara
Graphical abstract: Abstract: Despite the fact that 80% of adult acute myeloid leukaemia patients reach complete morphological remission after induction chemotherapy, many of them relapse. Many studies have shown that detection of minimal residual disease (defined as 'any detectable evidence of persistent leukaemic cells during complete morphological remission') has an added value in prediction of relapse and survival, and is more than just a surrogate marker for already known risk factors in AML. As such, the behaviour of the disease during treatment might become equally or even more important to decide whether or not an upgrade of treatment (such as an allogeneic stem cell transplantation) is necessary to improve outcome. However, there are still many open issues as to what the ideal time point is to measure MRD, which threshold is clinically significant, what sample (peripheral blood or bone marrow) should be used and how we can standardize tests so that results from different labs become comparable. This review gives an overview of currently available evidence regarding technical issues, prognostic impact and MRD-directed treatment in AML.